Design of antenna elements for EISCAT 3D's phased arrays - Isaksson, Gunnar (Luleå tekniska universitet, EISLAB, 2012)
Design of the basic crossed polarization antenna element in the VHF band for EISCAT 3D's phased arrays has resulted in two competing designs that has some similarities but also differences. The virtues of the designs and the sometimes arbitrary design decisions leading to them are further elaborated in this article. Godkänd; 2012; 20120905 (isagun)